Anioł – byt transcendentny czy figura poetycka? O funkcjach postaci anielskich w poezji Adriany Szymańskiej - Mazan-Mazurkiewicz, Alicja (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article constitutes the analysis of multiple presence of angelic topic in Adriana Szymańska’s poetry. The poetess applies liftiness; the angels presence is connected with sublimity. There is presence with literary and intertextual property (Rilkes’ angels). Moreover, one of the most important aspects of her creation is openess for religious side of reality. There is the reason, why angels appears in her poems so often. Sometimes they are being treated as real, supernatural beings. On the other hand, they could have been only a kind of poctic methaphor.